MENINGKATKAN KEMAMPUAN SIMBOL HURUF MELALUI PERMAINAN ULAR TANGGA PADA ANAK USIA 5-6 TAHUN DI DESA DUKUH KRAJAN RT 09 RW 01 KELURAHAN DUKUH KECAMATAN SIDOMUKTI KOTA SALATIGA - Erma Maqdalena; Ajeng Ayu Widiastuti (Satya Widya, 2018)
This study aims to improve the ability to recognize symbols of the letters through the game of snakes ladder in children aged 5-6 years in Desa Dukuh Krajan RT 09 RW 01, Kelurahan Dukuh, Kecamatan Sidomukti, Kota Salatiga. This research is a type of Action Research Research (PAR). This study uses the subjects of children aged 5-6 years, amounting to 5 children. Technique of collecting data by observation, documentation, and interview. Data analysis techniques using quantitative descriptive. The results of this study indicate that snakes ladder method can improve the ability to recognize symbols of letters. The increase of letter symbol recognition can be seen based on the increase of pre-action percentage because 53,33% increase in cycle I become 65,55%, in cycle II increase to 81,65%, so that learning can be said succeed because of its calculation. the percentage of the ability to recognize symbols shows 76%. Indicators used include children who can show the shape of the symbol (pre-writing), create a picture with some letters / posts that have been shaped letters, and write his own name.